2022
DOI: 10.3389/fendo.2022.922886
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Relationship of Sleep Quality and Duration With Risk of Diabetic Retinopathy

Abstract: ObjectiveA meta-analysis is used to explore the relationship of sleep quality and duration with the risk of diabetic retinopathy (DR).MethodCochrane Library, PubMed, Embase, and other databases are searched from their establishment to April 2022. Literature on the relationship of sleep quality and duration with DR risk published in various databases is collected, and two researchers independently screen the literature, extract data, and evaluate the quality of the included articles. The meta-analysis is perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…35 With regard to diabetes complications, a recent meta-analysis of 7 articles including more than 4500 people with diabetes found that low sleep quality related to a higher occurrence of diabetic retinopathy. 57 With respect to sleep problems, our meta-analysis showed that in those with T2D having insomnia (symptoms), there are higher HbA 1c levels (mean difference, 0.23% [0.1-0.4]) and higher fasting glucose levels (mean difference, 0.40 mmol/L [0.2-0.7]), 43 compared to those without insomnia. In addition, among people with T1D with moderate-to-severe OSA there was a trend toward higher HbA 1c levels (MD = 0.39%, 95% CI = −0.08, 0.87).…”
Section: Sleep Qualitymentioning
confidence: 88%
“…35 With regard to diabetes complications, a recent meta-analysis of 7 articles including more than 4500 people with diabetes found that low sleep quality related to a higher occurrence of diabetic retinopathy. 57 With respect to sleep problems, our meta-analysis showed that in those with T2D having insomnia (symptoms), there are higher HbA 1c levels (mean difference, 0.23% [0.1-0.4]) and higher fasting glucose levels (mean difference, 0.40 mmol/L [0.2-0.7]), 43 compared to those without insomnia. In addition, among people with T1D with moderate-to-severe OSA there was a trend toward higher HbA 1c levels (MD = 0.39%, 95% CI = −0.08, 0.87).…”
Section: Sleep Qualitymentioning
confidence: 88%
“…The inverse association between physical activity and the risk of diabetic complications may be attributed to reduced inflammation and elevated levels of 25-OH-Vitamin D3 [ 37 ].In this study, sleeping for less than 5 h was associated with an increased risk of DR. Sleep duration demonstrated a U-shaped association with diabetic vascular complications, with 6–8 h recommended for the lowest risk [ 38 ]. Beyond sleep deprivation, poor sleep quality has also been shown to impact the incidence of diabetic complication [ 39 ]. Potential mechanisms underlying these associations may involve sleep deprivation decreasing insulin sensitivity and enhancing systemic inflammatory responses due to circadian rhythm disruption [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Consequently, older adults may experience frequent complaints due to changes in their sleep patterns and quality.Poor SQ increases the risk of various physical and mental health problems. 5,6 Numerous studies demonstrated that poor SQ is associated with an increased risk of falls, cognitive disorders, dementia, reduced concentration, and mortality-related outcomes. [7][8][9][10][11][12] It is important to note that alterations in sleep patterns during the aging process can adversely affect the quality of life.…”
mentioning
confidence: 99%